2014
DOI: 10.1016/j.jgg.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Gαq, Gγ1 and Plc21C Control Drosophila Body Fat Storage

Abstract: Adaptive mobilization of body fat is essential for energy homeostasis in animals. In insects, the adipokinetic hormone (Akh) systemically controls body fat mobilization. Biochemical evidence supports that Akh signals via a G protein-coupled receptor (GPCR) called Akh receptor (AkhR) using cyclic-AMP (cAMP) and Ca(2+) second messengers to induce storage lipid release from fat body cells. Recently, we provided genetic evidence that the intracellular calcium (iCa(2+)) level in fat storage cells controls adiposity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…Consistent with the "adipokinetic" nature of the pathway, ablation of either the AkhR or the Akh gene impairs TAG mobilization in Drosophila (Grönke et al 2007;Bharucha et al 2008;Gáliková et al 2015;Sajwan et al 2015). Further, Drosophila genetic studies have also confirmed the crucial role of Ca 2+ in transmitting the Akh signal and identified the G proteins Gg1, Gaq, and the phospholipase C Plc21C as signal transducers along this axis (Baumbach et al 2014b). In addition, several proteins that either promote or antagonize intracellular Ca 2+ levels, such as the ER sensor Stromal interaction molecule (Stim), the plasma membrane channel Olf186-F, the ER Ca 2+ channels sarco/ endoplasmic reticulum Ca 2+ -ATPase (SERCA) and Itp-R83a, and the Ca 2+ -binding protein calmodulin (Cam), have been linked to TAG homeostasis in Drosophila (Baumbach et al 2014a;Bi et al 2014;Moraru et al 2017).…”
Section: Hormonal Control Of Drosophila Tag Metabolismmentioning
confidence: 70%
“…Consistent with the "adipokinetic" nature of the pathway, ablation of either the AkhR or the Akh gene impairs TAG mobilization in Drosophila (Grönke et al 2007;Bharucha et al 2008;Gáliková et al 2015;Sajwan et al 2015). Further, Drosophila genetic studies have also confirmed the crucial role of Ca 2+ in transmitting the Akh signal and identified the G proteins Gg1, Gaq, and the phospholipase C Plc21C as signal transducers along this axis (Baumbach et al 2014b). In addition, several proteins that either promote or antagonize intracellular Ca 2+ levels, such as the ER sensor Stromal interaction molecule (Stim), the plasma membrane channel Olf186-F, the ER Ca 2+ channels sarco/ endoplasmic reticulum Ca 2+ -ATPase (SERCA) and Itp-R83a, and the Ca 2+ -binding protein calmodulin (Cam), have been linked to TAG homeostasis in Drosophila (Baumbach et al 2014a;Bi et al 2014;Moraru et al 2017).…”
Section: Hormonal Control Of Drosophila Tag Metabolismmentioning
confidence: 70%
“…2; red components). Akh binding to AkhR triggers an inositol trisphosphate (IP3) second messenger response, which is relayed by small Gg and Gq protein subunits and phospholipase C (Plc21C) (Baumbach et al, 2014b). At the endoplasmic reticulum (ER) membrane, IP3 binding to the IP3 receptor (IP3R; called Itp-r83A in the fly) causes Ca 2+ efflux, which is sensed by an ER calcium sensor known as the Stromal interaction molecule (Stim, Fig.…”
Section: The Fat Body and Oenocytesmentioning
confidence: 99%
“…The AKHR is located in the plasma membrane of fat body adipocytes [ 69 ]. It was shown recently that AKHR uses G protein αq subunit (Gαq) and evokes Ca 2+ release as a second messenger system in the Drosophila adult fat body [ 107 ].…”
Section: Adipokinetic Hormones—main Stress Hormones In Insectsmentioning
confidence: 99%